“We do anything to get alcohol”: A mixed methods approach to explore the intersections between alcohol use and HIV risk and infection amongst adolescent girls and young women from high HIV-burdened communities in South Africa - Kate Bergh; Zoe Duby; Jeroen De Man; Nabila Ebrahim; Caroline Kuo; Carl Lombard; Petal Petersen Williams; Kim Jonas (PLoS ONE, 2026)
Despite national declines in HIV prevalence, adolescent girls and young women (AGYW) in South Africa continue to face a disproportionate burden of HIV infection. The syndemic theory provides a framework for understanding how interconnected epidemics such as alcohol use disorders, violence and HIV cluster together and reinforce each other. Using this theory, we aimed to test and explore the relationship between alcohol use and HIV risk and infection amongst AGYW in high HIV-burdened communities in South Africa. Data for this study were drawn from a mixed methods impact evaluation of a combination HIV prevention programme implemented across eight provinces in South Africa. A household survey was conducted among AGYW aged 15─24 years in the 12 intervention sub-districts selected by the Global Fund and 12 matching comparison sub-districts. Dried blood spot specimens were collected to test for HIV; alcohol use and sexual behaviours were reported through a self-completed electronic questionnaire. Generalised linear regression models were used to assess the relationship between alcohol use and HIV risk and infection as well as sexual risk behaviours and hazardous drinking. A subsample of 68 AGYW participated in qualitative in-depth interviews. Interview transcripts were translated into English and analysed using thematic analysis. Of the 5025 survey participants, 10% were living with HIV, and 35% engaged in hazardous drinking. No significant association was found between alcohol use and HIV risk or infection. However, a positive association was found between hazardous drinking and sexual violence (OR=1.51; 95% CI: 1.20─1.90), condomless sex (OR=1.25; 95% CI: 1.07─1.47), and condom counselling (OR=1.32; 95% CI: 1.14─1.53). Qualitative interview participants described how AGYW sought alcohol from older men, knowing that sex would be expected in exchange. This put them in high-risk situations where sexual violence was a concern and negotiating condom use became more challenging. These findings highlight the need for interventions that educate AGYW on the harmful effects of binge drinking and provide safer, healthier alternatives for recreation, particularly in low-resourced communities.